Evaluating the stock status of 10 croaker species landed along the north-eastern Arabian Sea using the length-based Bayesian biomass approach - Rahangdale, Shikha; Zacharia, Pariyappanal Ulahannan; Kumar, Rajan; Vase, Vinayakumar (Frontiers in Marine Science, 2022)
India accounts for nearly 60% of the croakers caught in the Indian Ocean. The north-west (NW) coast of India is the most productive fishing ground for croakers and contributes almost half of the nation's croaker catch. Lesser sciaenids (small and medium-sized croakers) are the multi-species complex landed by commercial trawlers along the NW coast of India. Despite several notable changes in the fishing pattern in the region such as the emergence of multi-day fishing and increasing dominance of pelagic trawling, there is no recent assessment of this major demersal fishery group. The present study evaluates the stock status of ten species of lesser sciaenids forming the commercial fishery in the region using length frequency data collected during 2020-21. The assessment was made using the Length-based Bayesian Biomass (LBB) estimation method. The indicators of relative biomass (B/B0 and B/BMSY) showed that most of the species (seven) are fully exploited, whereas two and one species were found under-exploited and over-exploited, respectively. Excessive juveniles (Lmean/Lopt and Lc/Lc_opt < 0.90) in catches were observed in the case of Paranibea semiluctuosa. A sufficient number of larger individuals (L95th/Linf< 0.90) in the population were lacking in the case of Johnius belangerii and Otoithes ruber. However, the study indicated a gradual improvement in stock status for most of the species over previous estimates, which can be attributed to the diversion of trawl fishing efforts towards the pelagic realm.